POLITIK HUKUM PIDANA PERTANGGUNGJAWABAN PIDANA KORPORASI DIKAITKAN SEBAGAI SUBJEK HUKUM PIDANA - Alfikri '; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Development of Globalization, has the potential to cause crimes / crimesin various fields carried out by actors both individuals and corporations that cancause losses and victims, which is supported by the emergence and developmentof science and information technology. The rarity of corporations that are used assuspects or defendants is certainly interesting to study and study. One of thecrucial problems is the difficulty of proving corporate criminal liability to fulfillthe criminal offense element violated by the corporation, because law enforcementofficials are still enforced on the principle of impunity without error which isindeed adhered to in the teaching of criminal responsibility in Indonesia. Thecorporate criminal liability system cannot be separated from the legislation policycontained in the legislationThis type of research can be classified in normative legal research, namelylegal research conducted by researching library materials. This study examinesthe subject matter in accordance with the scope and identification of the problemthrough a statute approach carried out by examining the laws and regulationsthat relate to the legal issue under study. In this study the authors conducted astudy of the principles of law by utilizing descriptive methods. Data collectiontechniques used in the Normative Legal Research are library research methods.The conclusion that can be obtained from the results of the study is thatcriminal law regulation on corporate criminal liability in criminal law cangenerally be classified into two, among others legislation that establishescorporations as the subject of criminal acts and can directly be asked for criminalliability (strict liability) and legislation that establishes the corporation as thesubject of a criminal act, however, the criminal liability is charged to themembers and management of the corporation (vicarious liability. PoliticalCriminal Law related to Corporate Criminal Accountability as a criminal lawsubject is an action carried out in several stages, namely the formulation stage(legislative policy), application stage (judicial policy), and execution phase(executive policy) .Three stages, the formulation stage is the most strategic stageof prevention and control of crime corporation